Analysis of the utilization of the SIDIGS platform in enhancing the quality of academic services - Nur Ratih; Tijanun Baroroh Addakhil; Muhamad iqbal Wibisono; Zainal Arifin Ahmad; Muhammad Andre Priatama (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
The development of information technology has encouraged schools to transform toward digital-based management. SMP Muhammadiyah 3 Depok (Mugadeta) faces challenges in improving the quality of academic services and has implemented SIDIGS (School Integrated Digital System) as an innovative solution. This study aims to analyze the utilization of SIDIGS in academic activities, its impact on service efficiency, and the challenges encountered in implementation. A qualitative approach with a single case study was employed, collecting data through in-depth interviews, observation, and documentation, then analyzed using Miles and Huberman’s interactive model with source and technique triangulation. The results indicate that SIDIGS supports learning management via the Learning Management System (LMS), digital attendance, school–parent communication, and financial administration. The system improves efficiency, accelerates access to information, strengthens digital work culture, and establishes a paperless school management ecosystem. Challenges include system disruptions, limited internet access, and varying digital literacy among users, addressed through regular training and evaluations. The study implies that effective digital transformation in schools depends on human resource readiness, adaptive leadership, and a responsive digital work culture.